Resiliensi Tahanan: Studi Literatur - Khosidah Khosidah; Megah Andriany (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2021)
Introduction: Prevalence of mental health problems including detainees in prison are very high. Handling mental health problems is closely related to the ability of resilience in a person. Limited study review resilience, factors influencing it and instruments used in detainee. This study aims to describe the resilience of detainees, instruments to measure it, and factors influencing the resilience of detainees.Methods: The research method used was literature review. Literature search was carried out using search keywords resilience, detainee, prison. The database used is SCOPUS, EBSCOHost, Garuda, Science Direct, ProQuest. Articles inclusion criteria are full-text articles from 2010-2020, published in English and Indonesian, and discussing resilience to detainees. Articles were identified using flow diagrams. Data were analysed using synthesis matrices.Results: The results of search that has been conducted stating that the instruments used to identify resilience levels consisted of the Connor and Davidson Resilience Scale (CD-RISC), the resilience quotient compiled by Reivich and Shatte, the Resilience Measurement Scale (RMS-25), the Adolescent Resilience Attitudes Scale (ARAS), and the Norwegian adaptation of Dispositional Resilience scale (DRS-15-R). The average level of resilience of detainees is in the medium category. Resilience is influenced by age, ethnicity, family relationships, social relationships, self-acceptance, protective factors (pro-social) and (pro-future). Detainees are prone to mental health problems, because they have moderate levels of resilience.Suggestion: Nursing services need to pay attention to the level of resilience of detainees.